Rancang Bangun Alat Ukur pH Dan Ketinggian Air Berbasis Smartphone Guna Meningkatkan Produktifitas Budidaya Ikan Nila - Affandi A; A R Nasution; I Tanjung; R S Harahap (Jurnal MESIL (Mesin Elektro Sipil), 2021)
The city of Medan constitutes one of the cities that has the potential for the development of freshwater fish farming, this is because it can help the economy and income for fish farmers. However, the lack of understanding of tilapia farmers on poor water quality conditions resulted in slow fish growth. Then the lack of monitoring time carried out by fish pond cultivators makes harvest yields also not optimal due to water conditions that can change at any time due to various factors, coupled with the maintenance process also causes a decrease in production yields, one of which is when infectious or non-infectious diseases occur. The objective of this program is to find out about understanding water conditions, pH, and water levels, as well as to assist the process of monitoring tilapia pond water automatically using a smartphone. The stages carried out, begin with problem investigation, problem analysis. Then design the measuring instrument and finally do the simulation/analysis of the tool. The results of this program have succeeded in making a smartphone-based pH and water level measuring instrument with simulation results showing the water level in the fish pond with an average of 2.4 and the average pH value of fish pond water being 7.1. However, in the development of further tools, it is necessary to manufacture a signal transmitter that supports the amplification of measuring devices in sending data to smartphones.